Gardens of Things: The Vicissitudes of Disappearance - Starosta, Anita (Intermédialités / Intermediality, 2007)
This essay traces the disappearance of the Soviet Union through aesthetical and everyday objects, and through an organization of the ethical and economic values that mark the so-called post-Soviet world. Looking through the different ways historical changes are mediated and made apprehensible, I propose to read Ryszard Kapuscinski's non-fictional account Imperium, Zbigniew Herbert's poems “Elegy for the Departure of Pen, Ink and Lamp” and “The Envoy of Mr. Cogito,” and Krzysztof Kieslowski's film No End (1984). I argue that the vicissitudes of disappearance question notions of historical rupture, making visible the processes of cultural renegotiation and reconstitution.